Huella hidríca por el uso del agua familiar en viviendas del asentamiento humana Micaela Bastidas, Loreto, Iquitos - Rodriguez Riva, Gilda Virginia (2022)
This study was developed in the Micaela Bastidas human settlement in the district of Iquitos, for which a representative sample of a population of 950 homes was taken to determine the water footprint for the use of family water in 76 homes. The interviewees were of legal age, with 40% over 56 years of age, 66% female, 59% with secondary education, where 80% noble material housing predominates. Regarding the family constitution by homes, 1 to 5 people predominate in 51%, the monthly billing for the water service was between 28 to 44 soles (37% of homes). The water footprint represented by the monthly consumption of water in homes, 43% consume between 3,000 and 6,000 liters of water approximately, which for the entire population under study represents a very high level of consumption (95% of homes), not very responsible about the responsible use of water in that area.